Reconstruction of the Criminalization Policy for Drug Abusers Based on a Public Health Approach in Indonesia - Abdul Azis Pangeran; M. Natsir (Siber Nusantara of Law and Politic Review, 2026)
This study analyzes the need for a reconstruction of drug abuse criminalization policies through a public health approach in response to the limitations of the penal paradigm that has dominated the Indonesian legal system. Imprisonment-oriented criminalization policies have proven ineffective in reducing dependency rates, do not suppress the prevalence of use, and actually worsen conditions in correctional institutions due to the surge in inmates from drug cases. Normative analysis shows that the Narcotics Law still contains overlapping criminal offense formulations, does not provide a clear differentiation between abusers and dealers, and lacks a binding rehabilitation mechanism, leaving its implementation dependent on the discretion of authorities. Theoretical studies show that addiction is a chronic relapsing disorder that requires long-term medical treatment, while public health principles such as harm reduction, treatment-first, and proportionality can form the basis for developing more humane and effective criminalization policies. Policy reconstruction is aimed at updating norms by redefining drug abusers, expanding mandatory rehabilitation programs, strengthening assessment obligations, and implementing institutional reforms, including coordination among the National Narcotics Agency (BNN), the Ministry of Health, and the Indonesian National Police (Polri) to establish integrated services. The ideal sentencing model emphasizes the integration of public health approaches, restorative justice, and modern sentencing theory to create a more recovery-oriented system for handling drug abusers. This research demonstrates that transforming sentencing policy is not merely a technical legislative requirement but a strategic step towards realizing the protection of rights, effective drug countermeasures, and balanced justice.